Deutsche Skulpturen. - Propyläen Refactur Berlin (Berlin : Propyläen Verlag, 1974)
Schadow, Johann Gottfried ; Wichmann, Ludwig Wilhelm ; Hoetger, Bernhard ; Kasper, Ludwig ; Stadler, Toni ; Marcks, Gerhard ; Seitz, Gustav ; Wotruba, Fritz ; Grzimek, Waldemar ; Hrdlicka, Alfred ; Schmettau, Joachim ; Schoenholtz, Michael ; Augustin, Edgar
Deutsche Skulpturen, Propyläen Refactur Berlin, 1974
boek